SPE Improved Oil Recovery Symposium 2014
DOI: 10.2118/169126-ms
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Stabilization of Foams by a Mixture of Nanoparticles and Surfactants

Abstract: The goal of this work is to evaluate stabilization of foams by a combination of nanoparticles and surfactants. Hydrophilic silica nanoparticles (NP) and anionic surfactants were used in this study. Static foams were generated using surfactants and surfactant-NP mixtures with and without the presence of a crude oil. The decay of the foam height with time was studied and half-lives were determined. The foam drainage behavior and thickness of the foam lamella were studied by fluorescence microscopy. Aqueous foams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…Similarly, Singh and Mohanty [136] reported that nanoparticle-surfactant solutions containing only about 0.3 wt.% nanoparticles significantly modified foam mobility ratio. The increase in nanoparticle concentration (0-5 wt.%) increased the mobility reduction factor from 4000 to 8700 and increased foam stability.…”
Section: Co 2 Storage and Leakage Inhibitionmentioning
confidence: 84%
“…Similarly, Singh and Mohanty [136] reported that nanoparticle-surfactant solutions containing only about 0.3 wt.% nanoparticles significantly modified foam mobility ratio. The increase in nanoparticle concentration (0-5 wt.%) increased the mobility reduction factor from 4000 to 8700 and increased foam stability.…”
Section: Co 2 Storage and Leakage Inhibitionmentioning
confidence: 84%
“…Nanoparticles are solid minerals, which are chemically more stable in a reservoir environment. They can show the same foam-generating properties as surfactant molecules, and can be used in synergy with surfactants (Singh and Mohanty 2014).…”
Section: Theorymentioning
confidence: 99%
“…The contact angle corresponding to the wettability of a nanoparticle adsorbed at the liquid-gas interface determines the stability of the foam generated by the nanoparticle suspension. A contact angle of 90 degrees provides maximum adsorption energy and therefore the highest stability (Singh and Mohanty 2014, Yu et al 2014, Binks 2002 . In addition, a (partially) hydrophilic particle can bridge the interface of a destabilizing foam lamella, and high concentration of the particles in the liquid phase at the Plateau border slows down the capillary drainage rate (Singh and Mohanty 2014).…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations